2011
DOI: 10.1158/0008-5472.can-10-3211
|View full text |Cite
|
Sign up to set email alerts
|

Human NK Cells Are Alerted to Induction of p53 in Cancer Cells by Upregulation of the NKG2D Ligands ULBP1 and ULBP2

Abstract: Natural killer (NK) cells are immune cells sensing and eliminating foreign, stressed, transformed, and senescent cells through specialized surface receptors, such as NKG2D, that interacts with several virus-or stressinducible ligands, including ULBP1 and -2, which are expressed on target cell surfaces. For example, induction of DNA damage or cellular senescence pathways in tumor cells led to upregulation of NKG2D ligands that activate NK cells. Although, both pathways activate p53, the relationship of p53 acti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
146
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 183 publications
(160 citation statements)
references
References 37 publications
4
146
4
1
Order By: Relevance
“…12 B7-H6 is expressed on the cell surface of many different tumor cell lines and on certain tumor cells in situ but not on hematopoietic cells from healthy individuals or primary keratinocytes. 12,15,25 So far, mechanisms that drive the expression of B7-H6 on tumors have not been elucidated. Several studies suggested that expression of activating NK cell ligands on tumors may be directly induced by oncogenes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12 B7-H6 is expressed on the cell surface of many different tumor cell lines and on certain tumor cells in situ but not on hematopoietic cells from healthy individuals or primary keratinocytes. 12,15,25 So far, mechanisms that drive the expression of B7-H6 on tumors have not been elucidated. Several studies suggested that expression of activating NK cell ligands on tumors may be directly induced by oncogenes.…”
Section: Discussionmentioning
confidence: 99%
“…NK cell isolation from healthy donors was performed as previously described. 25 NK cells were cultured overnight in CellGro Stem Cell Growth Medium (CellGenix) with 10% human AB serum (PAA) and 200 U/ml recombinant human interleukin 2 (IL-2, NIH). All media were supplemented with 100 U/ml Penicillin and 100 mg/ml Streptomycin (Sigma-Aldrich) and cell lines were routinely tested for contamination by the Multiplex cell Contamination Testing service at the German Cancer Research Center.…”
Section: Cells Reagents and Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, up-regulation of activating ligands and/or down-regulation of inhibitory ligands on tumor cells would increase NK cell activation against tumors. For instance, we showed that activation of p53 with the small molecular compound, RITA, led to the upregulation of ULBP1 and ULBP2 in tumor cells resulting in enhanced NK cell-mediated target recognition [47]. Similarly, certain MIC and ULBP proteins can be upregulated by the oncogene Ras [48] or by application of histonedeacetylase inhibitors [49,50].…”
Section: Introductionmentioning
confidence: 99%